2016
DOI: 10.1186/s12889-016-3854-7
|View full text |Cite
|
Sign up to set email alerts
|

Parental perception of built environment characteristics and built environment use among Latino families: a cross-sectional study

Abstract: BackgroundPerception of undesirable features may inhibit built environment use for physical activity among underserved families with children at risk for obesity.MethodsTo examine the association of perceived availability, condition, and safety of the built environment with its self-reported use for physical activity, we conducted a cross-sectional analysis on baseline data from a randomized controlled trial. Adjusted Poisson regression was used to test the association between the primary independent variables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…As part of the physical activity education, the HTC should identify barriers to participation including parenting practices and access to outdoor play space. The built environment is the “human made space in which people live, work, and recreate on a day‐to‐day basis.” The availability and upkeep of the built environment may impact participation in physical activities . Families may be scared to send their children out to play or may not be aware of accessible resources.…”
Section: Discussionmentioning
confidence: 99%
“…As part of the physical activity education, the HTC should identify barriers to participation including parenting practices and access to outdoor play space. The built environment is the “human made space in which people live, work, and recreate on a day‐to‐day basis.” The availability and upkeep of the built environment may impact participation in physical activities . Families may be scared to send their children out to play or may not be aware of accessible resources.…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies have indicated a discrepancy between actual physical distance and the known distance [8,47]. Consequently, numerous researchers prefer to set proximity thresholds in terms of time, ranging from 5 min (400 m) to 30 min (2400 m) as the ideal distance for walking [48,49], or to measure proximity according to territorial delimitations such as communities or districts (1200-1600 m) [48,[50][51][52][53][54][55][56], smaller areas such as neighbourhoods, not exceeding 10 min walking time [49,[57][58][59][60] or according to "activity areas" [61]. "[ .…”
Section: Accesibility (Perceived): Affordability Proximity Walkability Connectivity and Legibilitymentioning
confidence: 99%
“…Based on their perceptions about neighborhood food and physical activity environment, parents usually decide whether their child is allowed to play outside, walk or cycle to school, use neighborhood recreational facilities, and where to purchase foods [9]. For example, parental concerns about traffic safety and crime were associated with less time playing outdoors in primary school children [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis reported that high levels of crime were associated with a reduction in children's physical activity by 0.13 h per week [13]. Another study reported a positive association between parents' perceptions about greater availability and better condition of playgrounds and children's higher physical activity during leisure time [9] while a US study showed that greater parental satisfaction with the food shopping environment was associated with higher consumption of fruits and vegetables among 3-7 year-olds [14]. Furthermore, parents' satisfaction with the local food environment may affect home food availability and, consequently, what they feed their children [15][16][17].…”
Section: Introductionmentioning
confidence: 99%